Issues for animal production in developing economies: The case of sub-Saharan Africa - Anteneh, A. (Royal Agricultural Society of England, 1989)
Discusses issues for animal production in a developing economy context with particular reference to sub-Saharan Africa including emergent issues, economic policy issues, and research policy issues. Eamines role of livestock, performance and constraints. Highlights international and national agricultural research in sub-Saharan Afrca.